2020
DOI: 10.1038/s41431-020-0683-z
|View full text |Cite|
|
Sign up to set email alerts
|

Determination of the phylogenetic origins of the Árpád Dynasty based on Y chromosome sequencing of Béla the Third

Abstract: We set out to identify the origins of the Árpád Dynasty based on genome sequencing of DNA derived from the skeletal remains of Hungarian King Béla III (1172–1196) and eight additional individuals (six males, two females) originally interred at the Royal Basilica of Székesfehérvár. Y-chromosome analysis established that two individuals, Béla III and HU52 assign to haplogroups R-Z2125 whose distribution centres near South Central Asia with subsidiary expansions in the regions of modern Iran, the Volga Ural regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
5
15
0
2
Order By: Relevance
“…We could identify 30 derived mutations stemming from the hg R node and leading to hg R1a1a1b2a-Z95 plus an additional mutation on a downstream SNP, which defines Y chromosomal hg R1a1a1b2a2a-Z2123 (Table S6 ). This is a sub-hg of R1a1a1b2-Z93, the main Asian branch of R1a that has particularly high frequencies in Central Asia 46 , which is consistent with the result reported in previous studies 33 , 34 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We could identify 30 derived mutations stemming from the hg R node and leading to hg R1a1a1b2a-Z95 plus an additional mutation on a downstream SNP, which defines Y chromosomal hg R1a1a1b2a2a-Z2123 (Table S6 ). This is a sub-hg of R1a1a1b2-Z93, the main Asian branch of R1a that has particularly high frequencies in Central Asia 46 , which is consistent with the result reported in previous studies 33 , 34 .…”
Section: Resultssupporting
confidence: 93%
“…Olasz et al genotyped Y-STR haplotype of King Béla III and predicted he belonged to haplogroup (hg) R1a 33 . Nagy et al reported the Y chromosome sequence of Bela III and found the lineage traced to the region centering near Northern Afghanistan about 4500 years ago and the present-day Bashkirs were his closest paternal kin with a separation date about 2000 years ago 34 . Here, we attempted a genome-wide characterization of the remains of Bela III in order to address whether the genome of King Bela III groups within the gene pool of central Asians or present-day Hungarians.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we explored diploid markers in WGS data generated for Y-chromosome analysis from 79 individuals [ 8 ]. Analyses were performed with Polypheme software validated for HLA typing from NGS data [ 10 ] and set up for RBC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed description of WGS procedure is given in [ 8 ]. DNA samples were sonicated using a Covaris S220 Ultrasonicator to yield fragments with a median fragment length of 300 bps according to the manufacturer’s recommendations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation